If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9(x-3)=-10x
We move all terms to the left:
-9(x-3)-(-10x)=0
We multiply parentheses
-9x-(-10x)+27=0
We get rid of parentheses
-9x+10x+27=0
We add all the numbers together, and all the variables
x+27=0
We move all terms containing x to the left, all other terms to the right
x=-27
| 2x-4x=2x+10 | | 9x-18=3x-18 | | 2x2-4x+24=0 | | 180=5x+3x+16 | | b9-12=518 | | 4x2+9x+17=2x2-x+2 | | 1/5x+1/6=11 | | 11x-8=7x+64 | | −9+x/4=−7 | | y=5(-3)+18 | | −25x=10 | | 26-5v=4(4-3v) | | 9c-14=9c+11 | | 3/4=r-10/6 | | 4x-12=3x-8-9 | | 9+1=-2(6x-5) | | u²-7u+6=0 | | 4x+9+5x-9=7x-10 | | 9v=710v-4 | | (5y+6)-(5+4y)=11 | | 5x-12=4-5x-16 | | 16^6x=14^6 | | 5(18+5x)=35x+120 | | 0.5x+1.2=0.9x-2.4 | | n^=64 | | 10+8)2x+4)=8-x | | x−5/2=5 | | 3(x+4)+11=8x-5(x-3) | | 5x(2x+4)=10x-3+24 | | 5(x+4)=8(3x-7) | | –9j=–8j−10 | | -8x=14=-2(4x-7) |